Blocking connexin channels improves embryo development of vitrified bovine blastocysts†. Issue 2 (24th January 2017) - Ortiz-Escribano, Nerea; Szymańska, Katarzyna Joanna; Bol, Melissa; Vandenberghe, Lynn; Decrock, Elke; Van Poucke, Mario; Peelman, Luc; Van den Abbeel, Etienne; Van Soom, Ann; Leybaert, Luc
Abstract: Connexins (Cxs) are required for normal embryo development and implantation. They form gap junctions (GJs) connecting the cytoplasm of adjacent cells and hemichannels (HCs), which are normally closed but open in response to stress conditions. Excessive HC opening is detrimental for cell function and may lead to cell death. We found that hatching of in vitro-produced bovine embryos, matured in serum-containing conditions, was significantly improved when vitrification/warming was done in the presence of Gap26 that targets GJA1 (Cx43) and GJA4 (Cx37). Further work showed that HCs from blastocysts produced after oocyte maturation in the presence of serum were open shortly after vitrification/warming, and this was prevented by Gap26. Gap26, applied for the exposure times used, inhibited Cx43 and Cx37 HCs while it did not have an effect on GJs. Interestingly, Gap26 had no effect on blastocyst degeneration or cell death. We conclude that blocking HCs protects embryos during vitrification and warming by a functional effect not linked to cell death. Summary Sentence: Peptide targeting of connexins protects bovine blastocysts against vitrification/warming stress by preventing the opening of hemichannels that function as a leakage pathway.